Kepemimpinan Islam Periode Khulafaur Rasyidin (Abu Bakar, Umar bin Khattab, Utsman bin Affan, Ali bin Abi Thalib) - Setiyowati, Asih; Putri, Cikal Jiwani; Jannah, Feni Miftakhul; As’ad, Muhammad Rizaludin (YASIN, 2021)
This study describes the management of Islamic leadership during the Khulafaur Rasyidin period. The focus of this study discusses leadership management during the caliphate of Abu Bakr As-shidiq, Umar bin Khatab, Ustman bin Affan, and Ali bin Abi Talib. This study aims to analyze the management and leadership model of Islam during the Khulafaur Rasyidin era. The research was conducted using a review paper research method, where the researcher studied and understood the studies related to the title. The results of this study showed that after the death of the Prophet Muhammad SAW there was a vacancy in the leadership of Muslims and the Prophet did not leave a will who would continue his leadership because the Prophet gave everything to Muslims. The selection of Khulafaur Rashidin as the successor of the Prophet was carried out in two ways, namely deliberation and direct appointment. Abu Bakr's leadership model is central which continues to conduct deliberation, Umar applies a firm and coercive leadership model but still prioritizes humanity, Umar also always tries to create new policies that are beneficial for the people and the progress of Islam. During Uthman's leadership he managed to record the Qur'an and at the end of his leadership there was a rebellion that caused Uthman to be killed. Ali's leadership period was also inseparable from the rebellion.